Muatan Materi Pendidikan Pancasila Dalam Menumbuhkan Kesehatan Mental Peserta Didik Dan Implementasinya Dalam Pembelajaran - Bowo, Ahmad Nasir Ari; Nugroho, Taufik; Wahono, Joko; Restin, Omina; Esawati, Anastasia (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
Mental health problems of students include depression, emotional, fear, character, worry, and promiscuity. Teachers focus on theoretical material and have not deepened the mental health content. The formulation of the problem is: what are the contents of Pancasila Education material in fostering mental health? How is the implementation of Pancasila Education Learning in fostering mental health? The study used a qualitative exploratory multiple case study approach, at SMAN 1 Prambanan, MAN 2 Sleman, SMAN 3, and MAN 3 Bantul. Data sources are the principal/vice principal, teachers, and students. Data types: interviews, observations, documents. Data validity using triangulation techniques, interactive qualitative data analysis Miles & Huberman flow model. Research results: (1) the content of the material is developed according to the characteristics of students, including the formulation and actualization of Pancasila values, Bhineka Tunggal Ika, and the UUD constitution; (2) teachers guide, and motivate the importance of mental health, learning through projects, problem-based, and other active learning innovations.